Porous ceramics with controllable properties prepared by protein foaming-consolidation method - Fadli, Ahmad; Sopyan, Iis (Springer New York LLC, 2011)
A new protein foaming-consolidation method for preparing porous alumina was developed using egg yolk both as consolidating and foaming agent. This method allows the control of properties of porous alumina not only by varying alumina-to-yolk ratio but also by managing the foaming process. After drying, the green bodies were burned at 600 C for 1 h to remove the pore creating agent, followed by sintering at 1,550 C for 2 h. The porous alumina ceramics with pore sizes of 25–1,000 lm and relative density of 29–50% were obtained. The compressive strength of the sintered samples varied within the range of 1.1–5.7 MPa, corresponding to porosity of 40–71%. The addition of dispersant with different concentration into alumina slurries shifted the rheological properties from shear thinning behavior to a Newtonian fluid, which resulted in changes in the pore sizes of the resulting ceramics. The main advantages of the process are the simplicity of the process and the low-cost processing equipment/materials needed. These results have opened a novel preparative way for porous ceramics especially alumina-based porous materials designed for biomedical applications.